Does Exchange Rate Influence Trade Balance in Nigeria (1986-2022)? - Adekunle, Ahmed Oluwatobi (Yayasan Ilomata, 2024)
Due to trade balance disparities and the recession in numerous African nations, exchange rate discourse has recently gained prominence throughout the continent. Because of their high reliance on imports and limited production capacity, developing nations find it challenging to create enough foreign money to fund imports, which means that the exchange rate has an impact on their trade balance. Sequel to this, this paper examines the effect of exchange rate on trade balance in Nigeria between 1986 and 2021. Using ARDL methodologies, this study shows that exchange rates have a significant impact on trade balance, highlighting its critical role in the international finance of the country. The study recommends A policy that aims to depreciate the Nigerian exchange rate to improve the TrB can be advocated because the results indicate that a depreciation of the currency may have a positive impact on the TrB over the long term. However, this recommendation to devalue the Naira shouldn't be so drastic as to negatively impact the importation of capital goods that are vital to the expansion and development of the Nigerian economy.